Malaysian advertising: time for stock taking / Khairuddin Othman - Othman, Khairuddin (Faculty of Communication and Media Studies (FCMS), 2008)
The year 2008 may perhaps be remembered as an exhaustible experience to most Malaysians. After the loss of a solid three-quarter majority seats in Parliament by the ruling Barisan Nasional party, issues came in continuous avalanches.